PENGARUH BAURAN PEMASARAN TERHADAP KOMUNIKASI DARI MULUT KE MULUT MELALUI KEPUASAN PELANGGAN - Nurhadi Wijayanto (Universitas muhammadiyah malang, 2012)
Nurhadi WijayantoPT. JAMSOSTEK (Persero) Kantor Cabang PasuruanE-mail: Nurhadi_wijayanto@yahoo.comABSTRACTThis research represent quantitative research and it aims to analyse influence of marketing mix toword of mouth with customer satisfaction as intervening variable. By using two way of that is enquettemethod and of interview. The tool of analyses used Structural Equation Modelling (SEM). Result ofresearch indicate that marketing mix which consist of product, price, place, promotion, people, physicalevidence and process influenced to customer satisfaction at participant of program of Jamsostek. Indetail, those product variables namely price, place, promotion, and physical evidence have influencedsignificantly to customer satisfaction where as people variable and process did not influencesignificantly to customer satisfaction. The Customer satisfaction have influenced to word of mouth(WOM) at participant of program of Jamsostek. Marketing mix (product, price, place, promotion,people, physical evidence and process) have influence to word of mouth (WOM). Marketing mix didnot influence to word of mouth (WOM) directly but indirect influence to WOM. It mean that thecustomer satisfaction did not have synergy with marketing mix.Keyword: Marketing mix, customer satisfaction, word of mouth.